Australian pentecostal and charismatic movements : arguments from the margins - Hutchinson, Mark, 1958-; Openshaw, Kathleen; Rocha, Cristina (Global Pentecostal and Charismatic Studies, 2020)
"In Australian Pentecostal and Charismatic Movements: Arguments from the Margins, Rocha, Hutchinson and Openshaw argue that Australia has made and still makes important contributions to how Pentecostal and charismatic Christianities have developed worldwide. This edited volume fills a critical gap in two important scholarly literatures. The first is the Australian literature on religion, in which the absence of the charismatic and Pentecostal element tends to reinforce now widely debunked notions of Australia as lacking the religious tendencies of old Europe. The second is the emerging transnational literature on Pentecostal and Charismatic movements. This book enriches our understanding not only of how these movements spread worldwide but also how they are indigenised and grow new shoots in very diverse contexts".